2020
DOI: 10.1051/ro/2018095
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid algorithm Tabu Search – GRASP for wounded evacuation in disaster response

Abstract: Natural and triggered-disasters, have devastating and profound negative effects on human lives that require a speedy declaration of an emergency in order to minimize their severe consequences. Hence, a prompt disaster response, in addition to effective measures such as informed decision making, organized evacuation plan, right hospital selection, proper rescue vehicles, efficient resources assignment and timely vehicle scheduling are critical actions needed to organize successful secured operations that could,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…It has been proven that MSCN models are NP-hard [7,12,[15][16][17]27,36,37,46]. Hence, the literature review has seen several meta-heuristic algorithms that were suggested to solve these NP-hard problems [16,17].…”
Section: Solution Methodologymentioning
confidence: 99%
“…It has been proven that MSCN models are NP-hard [7,12,[15][16][17]27,36,37,46]. Hence, the literature review has seen several meta-heuristic algorithms that were suggested to solve these NP-hard problems [16,17].…”
Section: Solution Methodologymentioning
confidence: 99%
“…The linear assignment model is a binary programming model and is used widely in solving assignment problems. Generally, assignment problem is a certain kind of transportation problem and it was formulated as a binary integer linear programming; see [18]. The main application of the standard assignment problem is solving the problem of assigning 𝑛 jobs to 𝑛 peoples in an optimum manner so that the minimum cost or maximum profit is obtained.…”
Section: Introductionmentioning
confidence: 99%